ADVANTAGES OF USING ARTIFICIAL INTELLIGENCE TOOLS IN DEVELOPING RESEARCH COMPETENCE OF FUTURE ENGLISH TEACHERS - Nabikhonova Masturakhon Ibrohimkhon qizi (Bright Mind Publishing, 2025)
This article analyzes the theoretical foundations of using artificial intelligence (AI) tools to develop research competence in pre-service English language teachers. In the era of digital transformation, integrating modern technologies—particularly AI-based educational assistants—into teacher training programs has become an urgent priority. The paper explores how tools such as ChatGPT, Grammarly, and Elicit can enhance key research skills, including problem formulation, literature analysis, academic writing, and critical thinking. The influence of AI on learning processes and its role in supporting educational research are examined through methodological and theoretical perspectives. The article also provides practical recommendations for implementing AI-assisted strategies to foster research competence in language teacher education.
Keywords: Artificial intelligence, research competence, pre-service English language teachers, digital pedagogy, academic writing, critical thinking, innovative educational technologies.